The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.23907/2011.009
|View full text |Cite
|
Sign up to set email alerts
|

Shaken Infants Die of Neck Trauma, Not of Brain Trauma

Abstract: Shaken baby syndrome (SBS) is routinely diagnosed on the basis of a classic triad of autopsy findings, namely retinal hemorrhage, subdural hemorrhage, and anoxic encephalopathy. However, ongoing controversy exists regarding the specificity and potential causes of these signs, and hence their reliability as de facto markers of SBS, or of non-accidental head injury, where no external signs of trauma are evident. We investigated the deaths of 35 infants and young children, which fell into two broad groups: those … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
35
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 45 publications
0
35
0
Order By: Relevance
“…Although not evaluated in this model, the unilateral pattern of HH is unlikely to result from neck injury and/or nerve reflexes from the dura, which cause global apnea, a mechanism purported by Geddes and colleagues and others. 10,11,[41][42][43] An alternate possible mechanism is a regional metabolic mismatch between supply and demand. The exact pathophysiological mechanisms by which widespread unilateral hemispheric hypoxic-ischemic injury is initiated and propagated in children are not fully understood, but similar findings were produced in this model in the absence of angular acceleration/deceleration.…”
Section: Discussionmentioning
confidence: 99%
“…Although not evaluated in this model, the unilateral pattern of HH is unlikely to result from neck injury and/or nerve reflexes from the dura, which cause global apnea, a mechanism purported by Geddes and colleagues and others. 10,11,[41][42][43] An alternate possible mechanism is a regional metabolic mismatch between supply and demand. The exact pathophysiological mechanisms by which widespread unilateral hemispheric hypoxic-ischemic injury is initiated and propagated in children are not fully understood, but similar findings were produced in this model in the absence of angular acceleration/deceleration.…”
Section: Discussionmentioning
confidence: 99%
“…Six of these children had no evidence of impact to the head. In another study on fatal cases, Matshes et al [17] studied 35 children (newborns to 36 months of age) by removing the entire cervical spinal column and completing extensive dissection with microscopic evaluation. Of the 12 cases with hyperflexion/hyperextension (suspected or confirmed), all had bilateral or unilateral hemorrhages within or surrounding C3, C4, and/or C5 cervical spinal nerve roots.…”
Section: Discussionmentioning
confidence: 99%
“…The SBU report is a further addition to previous large‐scale judicial reviews undertaken in the UK (Goldsmith review, 2006) and in Canada (Goudge Inquiry, 2008), which concluded that the presence of the triad alone should not automatically lead to a diagnosis of SBS .…”
mentioning
confidence: 96%
“…The topic has never ceased generating heated controversy and acrimonious debates. At the core of the dispute is not whether shaking can cause devastating lethal injury, as it can certainly do . The main controversy resides in the value of the ‘triad’ as categoric evidence of abusive head trauma (AHT) by shaking when no other credible explanations are found.…”
mentioning
confidence: 99%